PENGEMBANGAN MEDIA GAMPITU DALAM PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA DAN KREATIVITAS SISWA PADA MATA PELAJARAN IPA DI KELAS IV SEKOLAH DASAR - Rosdiana; Yunus Abidin; Widiasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Students' low understanding of science learning concepts. This is caused by the presentation of unattractive teaching materials, which significantly reduces students' understanding of science concepts. This research aims to develop GAMPITU learning media products with a Project Based Learning design in science learning for grade IV elementary schools. This research uses the development of the DnD model with six development stages, namely identify the problem motivating the research (problem identification), describe the objective (describe the goal), design and develop the artifact (product design and development), subject the artifact to testing (trial product), evaluate the result of testing (evaluate test results), communicate those results (communicate test results). Based on the results of the research and development that has been carried out, it can be concluded that the GAMPITU learning media is given to teachers and students of class IV elementary schools whose implementation is based on project based learning. At the development stage, the results of product validation by teaching materials expert lecturers were 99.17%, technology experts were 92.5% and language experts were 90% and were declared feasible with slight revisions. Then the user response, namely teacher response as much as 94% and student response as much as 82% of students showed interest in Gampitu media and it can be stated that Gampitu media is considered practical and easy to use as a learning medium. Thus, GAMPITU learning media designed with PJBL is declared effective in increasing understanding of science concepts and fostering creativity in fourth grade elementary school students. Keywords: GAMPITU Media, PJBL, science understanding, student creativity